Análisis del presupuesto asignado y el presupuesto ejecutado por las municipalidades del departamento de Loreto periodo 2017 - 2021 - Clavo Perez, Renatto (2023)
Frequently, the municipalities of the department of Loreto demand a larger budget from the central government, since what they receive is not enough to finance activities and public works. The objective of this research is to analyze the budget assigned and the budget executed by the municipalities of the department of Loreto in the period 2017 - 2021. Based on this objective, the present Quantitative type study is carried out, Descriptive level and of non-experimental design. The investigation concludes that the municipalities did not execute the entire assigned budget but only 74.84%, showing inefficiency in budget management. Likewise, the budget execution by generic expense item was concentrated in Acquisition of Non-Financial Assets in 43.81%, equivalent to S/. 1,629,084,827.00. In the same way, analyzing the budget execution by source of financing, it has been possible to identify that it is concentrated in Determined Resources in 55.76%, which means in monetary values the sum of S/. 2,073,470,575.00. The second highest value source was Ordinary Resources with S/. 762,260,933.00; which represents 20.50% of the total. On the other hand, the budget allocation had a positive behavior in general terms, increasing at an average annual rate of 3.87%, with 2020 being the period in which the largest budget was allocated.